Potential sources of foreign language learning boredom: A Q methodology study - Kruk, Mariusz; Pawlak, Mirosław; Elahi Shirvan, Majid; Taherian, Tahereh; Yazdanmehr, Elham (Studies in Second Language Learning and Teaching, 2022)
The present study employed an interpretive approach to investigate individual learners’ viewpoints on foreign language learning boredom (FLLB). To this aim, a Q method, which shares features of both qualitative and quantitative research approaches, was used to explore 37 Iranian English as a foreign language (EFL) learners’ perceptions of potential sources of boredom in the classroom. Nonprobability purposeful sampling was used to select participants from two private language institutes in Mashhad, Iran. A hybrid-type Q sampling was employed to produce 40 statements related to the sources of FLLB. Using PQ Method, an exclusive statistical package for Q methodology, the Q sorts were intercorrelated and factor-analyzed. Three factors were extracted and rotated using varimax rotation and hand adjustment. Factor arrays and qualitative analyses were utilized to find and interpret three different accounts of FLLB. The three factors showed that the students held three divergent prototypical points of view about the sources of boredom experienced in EFL learning in class: (a) teacher-induced boredom, (b) student-induced boredom, and (c) activity-induced boredom. The findings also showed that different learner prototypes experience FLLB distinctly. Thus teachers should consider using different strategies to prevent or reduce this negative emotion in the context of L2 learning since otherwise this process could be impeded.